Incorporating big data within retail organizations: A case study approach. (May 2021) - Aversa, Joseph; Hernandez, Tony; Doherty, Sean
Abstract: The rapid growth in consumer-generated Big Data that are mostly sourced from various types of mobile devices and sensor technologies has placed increasing competitive pressure on retailers to leverage such data within their location decision-making practices. This paper examines the incorporation of Big Data within retail organizations. Through the analysis of three in-depth case-studies of major retail-related organizations operating in Canada, this research addresses the following two inter-related objectives: (i) to identify the awareness, availability, and development of Big Data environments; and, (ii) to explore the opportunities and challenges associated with new Big Data-based decision support systems within retail organizations. The characteristics of an ideal data environment for Big Data adoption and development to take place are identified. The key findings reveal that while there was general awareness of the importance of Big Data, it was evident that the adoption and development of Big Data decision support was heavily reliant on a data environment that promotes transparency and a clear corporate data strategy. Graphical abstract: Fig. 4Adoption Framework for Retail BD and BD Analytics. Image 1